STUDY AND ANALYSIS OF THE EFFECT OF THE CHARGE INITIATION METHOD ON STEMMING MOVEMENT IN A BLAST HOLE (European Journal of Interdisciplinary Research and Development, 2026)
A review of literary sources is presented, reflecting the efficiency and necessity of using stemming in blast holes during the explosive fragmentation of rocks, as well as the influence of the charge initiation method on rock fragmentation.